Progesterone modulates HSD11B1-mediated cortisol production in luteinized bovine granulosa cells - Memory MUKANGWA; Masafumi TETSUKA (The Society for Reproduction and Development, 2023)
Progesterone (P4) and cortisol production increase in luteinized granulosa cells (LGCs) during the periovulatory period, but their interaction is not well established. Therefore, we investigated their interaction in cultured bovine LGCs. Granulosa cells were collected from follicles of 2-5 mm in diameter and cultured in DMEM/F-12 supplemented with 10% fetal calf serum for up to 14 days. P4 production and the expression of steroidogenic acute regulatory protein (STAR), cholesterol side-chain cleavage enzyme (CYP11A1), and 3β-hydroxysteroid dehydrogenase type 1 (HSD3B1) rapidly increased until day 10 and remained high thereafter. No de novo production of cortisol from P4 was detected during the culture period. The expression of 11β-hydroxysteroid dehydrogenase type 1 (HSD11B1), which converts cortisone to cortisol, increased dramatically on day two, decreased until day 8, and remained relatively constant. To investigate how P4 and cortisol influence each other's production, LGCs were treated with trilostane (a P4 synthesis inhibitor), nomegestrol acetate (NA, a synthetic progestogen), P4, and/or cortisol for 24 h on days 6 and 12 of culture. Trilostane suppressed P4 and STAR expression while elevating HSD11B1 and HSD3B1 expression and cortisol production. Concomitant treatment with NA or P4 dose-dependently decreased cortisol production and HSD11B1 and HSD3B1 expression but elevated STAR expression in both days 6 and 12. Conversely, cortisol treatment increased HSD11B1 and HSD3B1 expression and decreased STAR expression without influencing P4 production. These results indicate that progestogens suppress cortisol production by modulating HSD11B1 expression and that progestogens and cortisol differentially regulate STAR, HSD3B1, and HSD11B1 expression in bovine LGCs.